"A false sister. A false foreigner": space, sexuality, and identity in Condé's Heremakhonon. Issue 1 (2nd January 2019) - Ward, Catherine
Abstract: Migratory journeys beget questions of the self. How does time spent in transit, intermeshed in varying cultures, affect one's identity? Moreover, how does it contribute to a character's understanding of home, that deceptively simple term pointing to so much more than just one's residence? Maryse Condé's Heremakhonon explores the effect spatial positioning has on identity through protagonist Veronica Mercier. The text, originally written in French, explores Veronica's triangular migration as a cultural, linguistic, and sexual journey in addition to merely geographical. Counterintuitive to expectations of migration, Veronica's journey is a privileged return, despite the presence of political chaos that often prompts forcible displacement. This paper will unpack the notion of home to explore the manner in which Veronica discovers that home and the associated power of ancestral roots are within, despite presumptions about home as place.